Foreign direct investment and globalization - Leitão, Nuno Carlos (2012)
The main objective of this article is to explain the link between foreign direct investment and globalization. The determinants of the location were used as market size, human capital, and urban population. Beyond these one institutional variable was introduced – the impact of global ization on FDI. The study applies a panel data approach (fixed effects and GMM system estima tor). The results show that market size and globalization have positive impact on FDI. Openness trade and urban population are also statistically significant.